HISTORICAL EXCURSION FOR THE DEVELOPMENT OF THE INFORMATION AND COMMUNICATION PEDAGOGICAL ENVIRONMENT - Petukhova, L.Ye. (Pedagogy of Higher and Secondary Education, 2010)
The becoming and development of the concept "informative-communicative pedagogical environment" is observed in the article in the context of historical civilization development.